NAPRECA newsletter - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
NAPRECA newsletter is the twice-yearly newsletter of the Natural Products Research Network for Eastern and Central Africa.